ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA PADA DESA TIKELA KECAMATAN TOMBULU KABUPATEN MINAHASA - Kasenda, Tirsa; Morasa, Jenny; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
There are three main objectives in government accounting, namely accountability, managerial and supervision. Government accountability is a manifestation of providing information about actions or activities of government financial management during that period. Village Fund Allocation comes from Transfer income sourced from the central and regional financial balance received by the district / city. This research was conducted in the village of Tikela Tombulu, Minahasa regency. in this study using a qualitative method of descriptive approach. The description was obtained through measurement by comparing the Minister of Home Affairs regulation number 113 year 2014 with actual field activities. The results based on the Minister of Home Affairs Regulation number 113 year 2014 indicate that the management of village fund allocations in Tikela is accountable and transparent. But there is still an implementation phase that needs to be improved to the principle of transparency. But it is also supported by people who actively participate in making rural development.Keywords: village fund management, accountability